An application of Green’s function for acoustic radiation of a source located near the two wall corner - W.P. Rdzanek; W.J. Rdzanek; K. Szemela (Archives of Acoustics)
This paper focuses on the problem of sound radiation of a time harmonically vibrating rectangular piston embedded into one of two baffles configured spatially as the two wall corner. The sound radiation pressure and sound radiation power, active and reactive, have been presented as their Fourier representations using the Green’s function. The directivity pattern has been expressed in terms of some elementary functions whereas the radiation efficiency has been expressed as a low frequency approximation. The elementary formulas obtained make it possible to clearly interpret the influence of the baffles of two wall corner on the sound radiation of the piston.